The Impact of Self-Narrative Framing of a Close Person's Sudden Death on Coping With the Meaning in Life. Issue 4 (19th May 2019) - Odachowska, Ewa; Trzebiński, Jerzy; Prusik, Monika
Abstract: Sixty-eight participants who lost a close one on a sudden death were assigned to one of two experimental conditions. They described own story of relations with the deceased person or answered a questionnaire regarding the mourning process. The effects of self-story construction were measured after 2 weeks and then 3 months. The self-story framing of the death increased meaning in life and stress-related growth, and decreased anxiety. The effects became most apparent 3 months after the story description. Higher plot structuring was related to lower anxiety and greater feeling of purpose in life.